The Morality of Bargaining: Insights from “Caritas in Veritate” - Murphy, James Bernard (2011)
Pope Benedict XVI’s 2009 Encyclical-Letter “Caritas in Veritate,” (CV) breaks some new ground in the tradition of Catholic social teaching. I argue that explicitly this document makes a call for a new theory of economic exchange. Whereas, the traditional scholastic theory of the “just price” was focused on “the principle of the equivalence in value of exchanged goods” (CV 35), a new theory of exchange must focus instead on “a metaphysical understanding of the relations between persons” (CV 53). True, Thomas Aquinas pioneered this new approach to the morality of exchange when he argued that the Golden Rule must take precedence over the logic of the just price: the relation between persons must trump the relation between the goods exchanged. Caritas in Veritate argues further for a new theory of exchange that combines elements of mutual gain with elements of gift-giving. Here again we see a revision of traditional scholastic theory in which every transaction was defined exclusively either as a unilateral gift (subject to norms of distributive justice and charity) or as a bilateral exchange (subject to norms of commutative justice). Benedict, by contrast, calls for a vision of economic life in which gift-giving and exchange are mixed, so that bargains are “redolent with the spirit of gift” (CV 37) in a new “economy of gratuitousness” (CV 38). I propose to outline a new theory of exchange in which the elements of mutual gain and gift-giving are combined. To do so, I shall have to revise the traditional scholastic analysis of the just price, which was focused on the equality of the goods exchanged and instead focus on the moral equality of the parties to an exchange.
Keywords: Just price; Exchange gift; ethics and economics; Catholic Social Teaching; Business ethics Caritas in Veritate; Benedict XVI; Bargain